2012
DOI: 10.1177/0960327112455070
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ubiquinone (CoQ10) on heart tissue in cardiac toxicity related to organophosphate poisoning

Abstract: The aim of this study was to examine the effects of ubiquinone (CoQ10) on heart tissue and erythrocytes in acute organophosphate poisoning (AOP). A total of 20 rabbits were divided into three groups: sham (n = 8), pralidoxime (PAM) + atropine (n = 6), and CoQ10 + PAM + atropine (n = 6). Blood samples were taken from each test subject to measure the values of acetylcholinesterase (AChE), nitric oxide (NO), and malondialdehyde (MDA) in the plasma and erythrocyte before administration of 50 mg/kg dichlorvos by or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The cardiovascular manifestation of OPC poisoning is mainly attributed to acute poisoning (23)(24)(25)(26)(27), which comprises bradycardia or tachycardia or impaired heart rate. There are reports showing an increased level of creatine kinases and lactate dehydrogenases, besides myocardial necrosis (28). The results of the present study reveal that TS causes a leakage of myocyte injury marker enzymes into the serum, as evidenced by the elevated levels of serum CK and LDH.…”
Section: Discussionsupporting
confidence: 63%
“…The cardiovascular manifestation of OPC poisoning is mainly attributed to acute poisoning (23)(24)(25)(26)(27), which comprises bradycardia or tachycardia or impaired heart rate. There are reports showing an increased level of creatine kinases and lactate dehydrogenases, besides myocardial necrosis (28). The results of the present study reveal that TS causes a leakage of myocyte injury marker enzymes into the serum, as evidenced by the elevated levels of serum CK and LDH.…”
Section: Discussionsupporting
confidence: 63%
“…There is a paucity of information available on the ability of CoQ 10 to ameliorate some of the adverse clinical effects associated with OP toxicity. However, a study by Bayir et al [51] reported the ability of CoQ 10 to attenuate OP induced cardiac toxicity. Furthermore, a recent study by Belousova et al [42] demonstrated that CoQ 10 improves neurological function in transient focal brain ischemia in rats [42].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular system affected by OP poisoning, cardiovascular manifestations include hypertension, sinus tachycardia, and bradycardia and reduced heart rate 4 . CF poisoning causes the heart tissue to produce high quantity of free radicals, become sensitive to oxidative stress, and damage 5 , these effects causes cardiovascular changes include an increase in cardiac marker enzymes level in serum; such as lactate dehydrogenase (LDH) and creatinine kinase-MB 6 . Because of CF widespread use, its residues detected in crops and in air 7&8 , which are considered dangerous to the living organisms 9 .…”
Section: Introductionmentioning
confidence: 99%